Hierarchically coated halide layers: enhancing the performance at composite cathode interfaces in solid-state Li-metal batteries - Jung, Jee Yun; Jeong, Hyeseong; Kim, Young Jung; Cho, Sung Man; Jang, Yongjun; Kim, Hyoungchul (Royal Society of Chemistry, 2024)
Despite the advances in new solid electrolytes (SEs) and processing technologies for solid-state Li-metal batteries (SSLMBs), the solid-phase interface in the SSLMB structure remains a challenge, impeding their commercialization. Here, we show that a hierarchically coated halide interface improves the material compatibility between a sulfide-based SE and an oxide-based cathode active material (CAM), thereby improving the performance of the SSLMBs. Li3InCl6 exhibits high reactivity with sulfides, whereas Li2.5Y0.5Zr0.5Cl6 exhibits low reactivity with sulfides and high reactivity with oxides. We designed a hierarchically coated interface structure and implemented it as an approximately nanoscale coating on the CAM. Compared to solely coated SSLMBs, the hierarchically coated cell shows significant improvements in various electrochemical performances, including the initial capacity, rate capability, and long-term cycling. The electrode area-specific resistance is suppressed to 137 Omega cm2 after 100 cycles at 0.5C, which is only 60-70% those of solely coated SSLMBs, consistent with the post-mortem quantitative results of interface products (P2Sx, In2S+, YO+, ZrO+). This strategy has potential to address the solid interface problem of SSLMBs and accelerate their commercialization. A hierarchically coated halide interface of composite cathodes in all-solid-state batteries improves material compatibility and electrochemical performance.